In vitro antioxidant and, α-glucosidase inhibitory activities and comprehensive metabolite profiling of methanol extract and its fractions from Clinacanthus nutans - Md. Ariful Alam; I.S.M. Zaidul; Kashif Ghafoor; F. Sahena; M. A. Hakim; M.Y. Rafii; H.M. Abir; M.F. Bostanudin; V Perumal; A. Khatib (BMC, 2017)
Abstract Background This study was aimed to evaluate antioxidant and α-glucosidase inhibitory activity, with a subsequent analysis of total phenolic and total flavonoid content of methanol extract and its derived fractions from Clinacanthus nutans accompanied by comprehensive phytochemical profiling. Methods Liquid-liquid partition chromatography was used to separate methanolic extract to get hexane, ethyl acetate, butanol and residual aqueous fractions. The total antioxidant activity was determined by 2,2-diphenyl-1-picrylhydrazy (DPPH) radical scavenging and ferric reducing antioxidant power assay (FRAP). The antidiabetic activity of methanol extract and its consequent fractions were examined by α-glucosidase inhibitory bioassay. The chemical profiling was carried out by gas chromatography coupled with quadrupole time-of-flight mass spectrometry (GC Q-TOF MS). Results The total yield for methanol extraction was (12.63 ± 0.98) % (w/w) and highest fractionated value found for residual aqueous (52.25 ± 1.01) % (w/w) as compared to the other fractions. Significant DPPH free radical scavenging activity was found for methanolic extract (63.07 ± 0.11) % and (79.98 ± 0.31) % for ethyl acetate fraction among all the fractions evaluated. Methanol extract was the most prominent in case of FRAP (141.89 ± 0.87 μg AAE/g) whereas most effective reducing power observed in ethyl acetate fraction (133.6 ± 0.2987 μg AAE/g). The results also indicated a substantial α-glucosidase inhibitory activity for butanol fraction (72.16 ± 1.0) % and ethyl acetate fraction (70.76 ± 0.49) %. The statistical analysis revealed that total phenolic and total flavonoid content of the samples had the significant (p < 0.05) impact on DPPH free radical scavenging and α-glucosidase inhibitory activity. Conclusion Current results proposed the therapeutic potential of Clinacanthus nutans, especially ethyl acetate and butanol fraction as chemotherapeutic agent against oxidative related cellular damages and control the postprandial hyperglycemia. The phytochemical investigation showed the existence of active constituents in Clinacanthus nutans extract and fractions.